Acute abamectin toxicity: a case report. Issue 1 (1st January 2021) - Pirasath, Selladurai; Nageswaran, Balasubramaniam; Vasana Karunasena, Rankiri Pathirannahalage; Gevakaran, Mathyasekeran
Abstract: Abamectin is a potentially fatal agricultural pesticide and antihelmenthic agent. Reports of human toxicity are rare. Here we describe a case of acute poisoning with an abamectin in an adult woman who presented with severe nausea, vomiting, altered consciousness, ptosis, mydriasis, and confusion. She recovered completely recovery with supportive care.